MODEL MATEMATIKA PERTUMBUHAN JUMLAH ANAKAN DAN TINGGI TANAMAN PADI YANG DITANAM DENGAN METODE SRI - Murtiningrum Murtiningrum; Willy Adi Purba; Sewan Delrizal Lubis; Wisnu Wardana (Faculty of Agricultural Technology, University of Jember, 2011)
The food requirement in Indonesia is highly dependent on rice and its requirement is increasing. On the other hand, the avalability of natural resource especially land and water are getting more limited. Consequently,there is a need to increase rice production with efficient resources. On the other hand, there is a necessity to apply sustainable agriculture. SRI (System of Rice Intensification) method was developed to deal with the problems. In the field, the SRI method still shows a wide variation of yields, therefore researches are necessary to reveal the phenomena behind this method. This paper aims to develop mathematical models of rice tillers and plant height of rice growth as well as to compare the growth of rice plants at several locations and treatments. Mathematical models developed were the rice tillers’ growth model which follow the exponential polynomial function order 2 and the crop heights model which follow the monomolekuler function. The number of seedlings from one seed planted in SRI would result more tillers than conventional crops after more than 30 days after planting. Conventional crop height was relatively higher than that of SRI because close spacing and inorganic fertilizers trigger vegetative growth.Keywords: mathematical model, SRI, crop physiology, rice